THE TOXICITY TEST OF Channa striata SCALE CHITOSAN ON BHK-21 FIBROBLAST CELLS IN VITRO - Muhammad Irfan Fanshuri; Deby Kania Tri Putri; Aulia Azizah; Juli Harnida Purwaningayu (Dentino : Jurnal Kedokteran Gigi, 2022)
Background:Regarding to the data generated by Basic Health Research in 2018, the prevalence of Indonesian people with dental and oral problems was amounted to 57.6%. Haruan fish scale chitosan has been shown to be capable of inhibiting growth and killing microorganisms that cause oral disease and has the potential to become a safe biomaterial. Toxicity testing was carried out to ensure safety of the chemical compounds before they can be used as drugs or during clinical trials. Purpose:This research was intended to analyze the toxicity of haruan fish scales (Channa striata) chitosan on BHK-21 fibroblast cells by utilizing the MTT assay method. Method:This research was classified as a true experimental research by adopting a post-test-only design with a control group design consisting of 6 groups. The treatment of haruan fish scale chitosan was given to 4 groups with concentrations of 25%, 50%, 75%, and 100%, with 2 control groups, specifically cell control and media control. The absorbance value was read by means of ELISA reader and the percentage of cell viability was subsequently calculated. The results of the average percentage of cell viability were then analyzed using SPSS to obtain the IC50 value. Result:The calculation of the average cell viability of each concentration was successfully obtained in this research. The average cell viability at 25% concentration was 2.106%, at 50% concentration was 12.01%, at 75% concentration was 77%, and at 100% concentration was 80.194%. The average percentage of cell viability data was further entered into the SPSS software and the value of IC50> 1000 µg/mL was successfully obtained. Conclusion: Haruan fish chitosan (Channa striata) is not toxic to BHK-21 fibroblas cell. Keywords : Channa striata , Fibroblast cell, Scale chitosan, Toxicity test.